Competitive work environments and social preferences: field experimental evidence from a Japanese fishing community - Jeffrey P. Carpenter; Erika Seki (Institute for the Study of Labor (IZA), 2005)
Models of job tournaments and competitive workplaces more generally predict that while individual effort may increase as competition intensifies between workers, the incentive for workers to cooperate with each other diminishes. We report on a field experiment conducted with workers from a fishing community in Toyama Bay, Japan. Our participants are employed in three different aspects of fishing. The first group are fishermen, the second group are fish wholesalers (or traders), and the third group are staff at the local fishing coop. Although our participants have much in common (e.g., their common relationship to the local fishery and the fact that they all live in the same community), we argue that they are exposed to different amounts of competition on-the-job and that these differences explain differences in cooperation in our experiment. Specifically, fishermen and traders, who interact in more competitive environments are significantly less cooperative than the coop staff who face little competition on the job. Further, after accounting for the possibility of personality-based selection, perceptions of competition faced on-the-job and the treatment effect of job incentives explain these differences in cooperation to a large extent.
Keywords: C90; C93; H41; M54; Z13; 330; field experiment; cooperation; social disapproval; social preference; competition; Japan; fishing; Fischerei; Wettbewerb; Kooperation; Japan; Feldforschung